Diampuni Untuk Mengampuni Sebagai Pendampingan Pastoral Kepada Anggota Jemaat Di GMIM Efata Tompaso - Kawengian, Karnia Mariana (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
Forgiveness is a GOD’s gift. According to the Bible, Jesus teaches His people to be able to forgive others’fault. Jesus not only taught about it, but also did it first when He forgave human and redeemed them from their sins. So, Jesus become the central figure in Forgiveness thing. Forgiving others is not easy to do even hard to do, because of we as human often cannot practice love for other, moreover forgiveness is same with practice love in difficult situation. Over and over again someone or a person tries to be able to forgive others’fault, but the most important thing is to ask GOD’s guidances. Because the forgiveness of others can be done if GOD grants to His people the ability to do that. That’s why forgiveness is (to be said as) GOD’s gift, and to get this gift, we are required to rely and surrender to GOD only. So in any circumstances of life, the practice of love can be done although in difficult place or in difficult situation, like loving people whose guilty to us by forgiving their mistake.